ANALISIS PENERAPAN METODE OBJECT POOLING PADA GAME 2D ENDLESS RUNNER - Aditya Cipta Rahadian; Iwan Setiawan; George Pri Hartawan (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
In this era of rapid technological development, many things are developing rapidly, one of which is the development of games in the world. Many games have been made by the developers themselves, so there are already many variations of the type of game itself, one of which is the endless runner genre game. In the endless runner game itself, there is an object that we have to create massively and repeatedly which usually applies to how to create and delete these objects massively. However, there is a better method in optimizing the implementation for massive object creation and deletion with the object pooling method, where the difference is in this method uses how to activate and deactivate objects. So in this way, it will optimize the game so that its performance does not drop and memory usage does not take up much space.